Mali : a prospect of peace? - Drisdelle, Rhéal (Oxfam country profile., 1997)
Looks at the lives of ordinary Malians and asks how they are surviving the changes which are transforming their nation. Also celebrates the culture of Mali, from village story-tellers to world-famous film makers and musicians.